2021
DOI: 10.1182/bloodadvances.2020003726
|View full text |Cite
|
Sign up to set email alerts
|

Reduced-intensity conditioning hematopoietic stem cell transplantation for chronic lymphocytic leukemia and Richter’s transformation

Abstract: Allogeneic hematopoietic stem cell transplantation (HSCT) may potentially cure patients with chronic lymphocytic leukemia (CLL) and Richter’s transformation (CLL-RT) or CLL without RT, but the impact of novel agents on HSCT is unclear. CLL-RT patients have a grave prognosis, and their outcomes after HSCT are uncertain. We conducted a retrospective analysis of all 58 CLL patients, including 23 CLL-RT patients, who underwent reduced intensity conditioning (RIC) HSCT at Memorial Sloan Kettering Cancer Center (New… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…Young age (<60 years), deeper response at SCT and having received <3 previous lines of therapy positively correlated with outcomes, while cytogenetic/molecular features and exposure to novel agents did not show an impact on PFS/OS ( 77 , 78 ). Total body irradiation (TBI) resulted in poorer outcomes ( 77 ).…”
Section: Treatment Of Dlbcl-rtmentioning
confidence: 97%
See 1 more Smart Citation
“…Young age (<60 years), deeper response at SCT and having received <3 previous lines of therapy positively correlated with outcomes, while cytogenetic/molecular features and exposure to novel agents did not show an impact on PFS/OS ( 77 , 78 ). Total body irradiation (TBI) resulted in poorer outcomes ( 77 ).…”
Section: Treatment Of Dlbcl-rtmentioning
confidence: 97%
“…A single-center retrospective analysis of 23 RT patients undergoing reduced intensity conditioning (RIC-SCT) reports a 5-year PFS of 40% and OS of 58% ( 77 ). Young age (<60 years), deeper response at SCT and having received <3 previous lines of therapy positively correlated with outcomes, while cytogenetic/molecular features and exposure to novel agents did not show an impact on PFS/OS ( 77 , 78 ). Total body irradiation (TBI) resulted in poorer outcomes ( 77 ).…”
Section: Treatment Of Dlbcl-rtmentioning
confidence: 99%
“…The 3 year OS was estimated at 36% for allogeneic SCT and 59% for autologous SCT, with an age younger than 60 years, chemo-sensitive disease, and RIC being associated with a better prognosis after allogeneic SCT in RT [77]. The benefits of RIC preceding allogeneic SCT in RT were also underlined in a recent retrospective study including 58 CLL patients, 23 of them with RT with a median follow-up of 68 months that revealed a 5 year OS of 58% and a 5 year PFS of 40% [78]. Another single center study showed encouraging results in 10 patients with RT referred to allogeneic SCT after objective response to therapy, with a 4 year OS of 50%, a non-relapse mortality at both 1 and 4 years post-transplantation of 40%, and a 4 year incidence of relapse/progression of 10% [79].…”
Section: Stem Cell Transplantationmentioning
confidence: 99%
“…The key clinical features associated with an improved PFS/OS following RIC alloSCT were treatment-sensitive response and ≤3 lines of prior therapy at alloSCT. Use of total body irradiation (TBI) containing RIC regimens was associated with an inferior PFS, OS, and relapse-free survival ( 58 ).…”
Section: Allosct For Cll In the Targeted Inhibitor Eramentioning
confidence: 99%
“…The 1-year NRM remains significant at 12%–23%. In both groups, one-third of the patients relapsed within 3–5 years ( 58 , 61 ).…”
Section: Allosct For Richter Syndromementioning
confidence: 99%